Pengembangan Prototype Remote Control untuk Fault Simulator Trainer - Pelawi, Jan Putra Bahtra Agung S; Yulianto, Andik (Telcomatics, 2023)
Most trainer module equipped a system error simulator (Fault Simulator), to activate the fault simulator the instructor must press a button that will bring up a certain type of fault that the trainer wants to simulate, then students will analyze the source of the error and fix it. The weakness of this trainer is that teachers must press a button on the trainer when they want to change the fault simulator in front of students so that participants will know which type of fault simulator is being run without troubleshooting. If this happens, the teaching objectives are not achieved so that the teaching process using this trainer becomes less effective. To overcome this problem, a remote-control prototype for trainers was designed consisting of an infrared (IR) based transmitter and receiver. To facilitate integration of the fault simulator module, the IR Transmitter and IR Receiver will communicate serially. From the tests carried out, it can be concluded that the designed remote-control prototype for trainers is functioning properly. IR transmitter and IR receiver can communicate serially using infrared media. This remote-control prototype has an optimal distance in the range of 0-5 m.